TINJAUAN MAQASID SYARI’AH TERHADAP ANGCIU YANG DIOLAH DALAM MAKANAN - Azizah, Nur; Fauza, Muflihatul; Husna, Nurul (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2024)
This study aims to provide an overview of the use of angciu used in processed food. The method used is qualitative through netnography tracing halal influencer accounts such as: @dianwidayanti, @aishamaharani, @anca.id. The source of data from this research is in the form of journals, online websites related to Angciu. The results that the author found that the use of angciu in food will affect the maqasid of sharia especially in terms of hifdz aql, which is the main center for humans. If angciu products are contaminated with something halal, it will cause halal food to become haram in consumption. Angciu is an ingredient that contains substances berifat khamr, in the sense that the alcohol contained in angciu itself as much as 17% and they cooks still use, it, because they think that this angciu can add a special flavor to the dish. just as the seller does not know about it, so is the buyer whose level of awareness of Islamic law is low against the prohibition of angciu.